Ukraina i stosunki transatlantyckie - Kiwerska, Jadwiga (Rocznik Integracji Europejskiej, 2015)
Europe/the European Union, with its obvious trump cards, should be an active and efficient player on the international arena. Such are the expectations of the United States, formulated especially by the administration of Barack Obama. However, from the American perspective, the EU has not proved successful as an important international actor, engaged in resolving global problems and prepared to assume greater responsibility for the course of events in the world. This inertia of the EU resulted in the marginalisation of Europe in American politics, as manifested by the latter’s pivot to the Pacific Rim. It was only after the developments in the Ukraine, which resulted from Russia’s imperial tendencies, that a greater activity and coherence in American and European politics was triggered, having a positive influence also on transatlantic relations.